Management of hypertension in adults - HSTN (Carrollton : HSTN, 1999)
Untreated hypertension can lead to such serious conditions as generalized arteriolar sclerosis, nephrosclerosis, left ventricular hypertrophy, and even stroke. This program features a comprehensive look at the physiology of hypertension . It surveys effective management of hypertension, from lifestyle changes to drug therapy, and highlights such new treatments as prolonged-release drugs
Keywords: Hypertension -- diagnosis; Hypertension -- therapy